Caracterización de señales de electroencefalografía(EEG) a estímulos musicales (2024)
This study investigates the effects of different musical genres on electroencephalographic (EEG) responses in healthy subjects. EEG, a technique for recording the brain's electrical activity, is used in Brain-Computer Interfaces (BCIs) to facilitate communication between the brain and external devices. The research highlights how various music styles, such as classical, rock, jazz, and vallenato, influence brainwave patterns differently.